Mechanisms of drug resistance in ovarian cancer - Żak, Klaudia; Piwoński, Michał; Stanicki, Paweł; Kalicka, Karolina; Nowaczek, Justyna (Journal of Education, Health and Sport, 2021)
Ovarian cancer is the fifth most common cancer affecting women and the most lethal cancer among the gynecological cancers. Because of the lack of specific symptoms and no special screening tools, it is recognised in an advanced stage. In addition, drug resistance in ovarian cancer is so frequent, that genes and cross-talks between some important pathways are still analysed. In this review, the major and recently identified molecular mechanisms of drug resistance, including platinum, taxane, bevacizumab and PARPi resistance mechanisms in ovarian cancer from relevant literature have been investigated.